Methanol electrooxidation at NiCl2–FeCl3–graphite intercalation compound affected by ozone treatment. (October 2021) - Rozmanowski, T.; Krawczyk, P.
Abstract: A graphite intercalation compound (GIC) incorporating nickel(II) and iron(III) chlorides (NiCl2 –FeCl3 –GIC) has been prepared, and the effect of ozone treatment on its catalytic activity towards methanol electrooxidation has been examined. The NiCl2 –FeCl3 –GIC was synthesized by a molten salt method, combining purified flaky graphite with the anhydrous metal chlorides. The obtained product was then modified with gaseous ozone. The crystalline structures and morphologies of the investigated compounds have been characterized by XRD and SEM/TEM techniques, respectively, and the results of these analyses have shown that ozone treatment of NiCl2 –FeCl3 –GIC contributes to changes in its structure and morphology. The process of methanol oxidation at both original and ozone-modified NiCl2 –FeCl3 –GIC electrodes has been examined in an alkaline electrolyte by means of cyclic voltammetry and a potentiostatic method. Electrochemical results have revealed that NiCl2 –FeCl3 –GIC exhibits activity towards the process of methanol electrooxidation. Furthermore, it has been proved that the electroactivity and durability of NiCl2 –FeCl3 –GIC are significantly increased following its ozone modification. Graphical abstract: Image 1 Highlights: Binary NiCl2 –FeCl3 –GIC with a mixture of stages-4, 5, and 6 has been obtained. Ozone treatment of NiCl2 –FeCl3 –GIC leads to structural and morphological changes. The electrochemical activity of NiCl2 –FeCl3 –GIC is enhanced after ozonation.